60Co-γ Radiation Alters Developmental Stages of Zeugodacus cucurbitae (Diptera: Tephritidae) Through Apoptosis Pathways Gene Expression. Issue 5 (29th October 2021) - Ahmad, Shakil; Hussain, Adil; Ullah, Farman; Jamil, Momana; Ali, Asad; Ali, Saqib; Luo, Yanping
Abstract: Radiation is considered as a promising insect pest control strategy for minimizing postharvest yield losses. Among various techniques, irradiation is a method of choice as it induces lethal biochemical or molecular changes that cause a downstream cascade of abrupt physiological abnormalities at the cellular level. In this study, we evaluated the effect of 60 Co-γ radiation on various developmental stages of Zeugodacus cucurbitae Coquillett and subsequent carry-over effects on the progeny. For this purpose, we treated eggs with 30- and 50-Gy radiation doses of 60 Co-γ. We found that radiation significantly affected cellular antioxidants, insect morphology, and gene expression profiles. Our results indicate that in response to various doses of irradiation reactive oxygen species, catalase, peroxidase, and superoxide dismutase activities were increased along with a significant increase in the malondialdehyde (MDA) content. We observed higher mortality rates during the pupal stage of the insects that hatched from irradiated eggs (50 Gy). Furthermore, the life span of the adults was reduced in response to 50 Gy radiation. The negative effects carried over to the next generation were marked by significantly lower fecundity in the F1 generation of the irradiation groups as compared to control. The radiation induced morphological abnormalities at the pupal, as well as the adult, stages. Furthermore, variations in the gene expression following irradiation are discussed. Taken together, our results signify the utility of 60 Co-γ radiation for fruit fly postharvest management.